The Relationship between Parental Permissive Parenting Tendencies and Sibling Rivalry in Early Adolescent Girls - ., Zahwa; Daud, Muh. (Polteknik Ilmu Pemasyarakatan, 2024)
Sibling Rivalry that occurs in adolescents refers to rivalry, conflict and competitive feelings. Bad relationships due to sibling rivalry cause children to hate each other, damage each other's property and tattle on each other. The purpose of this study was to determine the relationship between parental permissive parenting tendencies and early adolescent female sibling rivalry. Respondents in this study totaled 294 early adolescent girls. The sampling technique in this study used purpose sampling. The measuring instrument used is the sibling rivalry scale and permissive parenting. Hypothesis testing using the person product moment test shows a correlation coefficient with a value of r = 0.622 with a significant level of 5% (p>0.05) which means that there is a relationship between the tendency of parental permissive parenting and sibling rivalry in early adolescent girls. The implication in this study is that parents with permissive parenting are expected to balance their approach to children by providing clear boundaries and providing understanding to children to love each other in order to create a harmonious family environment and avoid sibling rivalry.